Measurement accuracy and reliability of tooth length on conventional and CBCT reconstructed panoramic radiographs - Carlos Flores-Mir; Mark R Rosenblatt; Paul W. Major; Jason P. Carey; Giseon Heo (Dental Press Editora, 2014)
INTRODUCTION: This in vivo study assessed accuracy and reliability of tooth length measurements obtained from conventional panoramic radiographs and CBCT panoramic reconstructions to that of a digital caliper (gold standard). METHODS: The sample consisted of subjects who had CBCT and conventional panoramic radiographic imaging and who required maxillary premolar extraction for routine orthodontic treatment. A total of 48 teeth extracted from 26 subjects were measured directly with digital calipers. Radiographic images were scanned and digitally measured in Dolphin 3D software. Accuracy of tooth length measurements made by CBCT panoramic reconstructions, conventional panoramic radiographs and digital caliper (gold standard) were compared to each other by repeated measures one-way ANOVA with Bonferroni correction and by single measures intraclass correlation coefficient. RESULTS: Repeated root length measures with digital calipers, panoramic radiographs and CBCT constructed panoramic-like images were all individually highly reliable. Compared to the caliper (gold standard), tooth measurements obtained from conventional panoramic radiographs were on average 6.3 mm (SD = 2.0 mm) longer, while tooth measurements from CBCT panoramic reconstructions were an average of 1.7 mm (SD = 1.2 mm) shorter. CONCLUSIONS: In comparison to actual tooth lengths, conventional panoramic radiographs were relatively inaccurate, overestimating the lengths by 29%, while CBCT panoramic reconstructions underestimated the lengths by 4%.